Amamiichthys, a new genus for the sparid fish Cheimerius matsubarai Akazaki 1962, and redescription of the species, with designation of a neotype - Tanaka, Fumiya; Iwatsuki, Yukio (Zootaxa, 2015)
A new genus, Amamiichthys, is proposed for the sparid fish Cheimerius matsubarai Akazaki 1962. This genus differs from all other genera in the family Sparidae by the following combination of characters: both jaws with an outer row of small molariform teeth and an inner row of similar, even smaller teeth; frontal bone flat, coarse and porous; strongly bifurcate protuberance of upper ethmoid just beneath mid-region of anteriormost portion of frontal bone; head and body pinkish, gradually becoming silvery toward abdomen, with many small blue spots, some pairs overlapping. The type species, Amamiichthys matsubarai, is redescribed and a neotype designated.